ANALISIS LEGAL DRAFTING PERATURAN KOMISI PEMILIHAN UMUM (PKPU) DALAM SISTEM PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Anida Kharamah; Birro Tiya; Ahmad Zaki Yamani (Yayasan Pendidikan Literasi Borneo, 2026)
This research is motivated by the importance of regulations in the Indonesian election system, particularly the General Election Commission Regulation as a technical legal instrument that regulates the implementation of elections to ensure fairness, orderliness, and democracy. The purpose of this study is to analyze the quality of the drafting of the General Election Commission Regulation within the legal system and assess its compliance with the principles of good legal drafting. This study uses a qualitative approach with a literature review method through a normative juridical approach combined with a conceptual and political legal approach. The results show that the drafting of the General Election Commission Regulation has fulfilled the requirements of systematic regulatory drafting techniques, a clear normative structure, and the use of clear and non-multi-interpretable legal language. In addition, this regulation plays a significant role in ensuring legal certainty and supporting the orderly and systematic implementation of elections. However, ongoing efforts are still needed to maintain regulatory harmonization and improve the quality of drafting to remain adaptive to legal dynamics and community needs. Thus, it can be concluded that the quality of legal drafting of the General Election Commission Regulation plays a strategic role in supporting the effectiveness and integrity of election administration in Indonesia.